2020
DOI: 10.3390/jcm9082416
|View full text |Cite
|
Sign up to set email alerts
|

The Reality of Patient-Reported Outcomes of Health-Related Quality of Life in an Italian Cohort of Patients with Inflammatory Bowel Disease: Results from a Cross-Sectional Study

Abstract: Inflammatory bowel disease (IBD) has a negative impact on patients’ physical and psychological well-being, social performance, and working capacity, thereby worsening their health-related quality of life (HRQoL). Clinicians should take care of the patients’ global health, including the psychological, social, and emotional spheres. We aimed to investigate the reality of patient-reported outcomes of HRQoL in a series of IBD patients. Consecutive Crohn´s disease (CD) and ulcerative colitis (UC) patients in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Literature supports the association between anxiety and gastrointestinal symptoms (GISs) [ 10 , 11 ]. In subjects with functional gastrointestinal disorders, such as dyspepsia and irritable bowel syndrome, the presence of anxiety seems to play a major role in the genesis and the perception of symptoms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature supports the association between anxiety and gastrointestinal symptoms (GISs) [ 10 , 11 ]. In subjects with functional gastrointestinal disorders, such as dyspepsia and irritable bowel syndrome, the presence of anxiety seems to play a major role in the genesis and the perception of symptoms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the METS decreased in subjects with severe GSRS symptoms. This reduction could be attributed to different reasons, such as stress factors [ 31 , 32 , 33 , 34 ], new conditions imposed by the constraint period, overtraining, or incorrect training [ 8 , 35 ]. Due to these conditions, the possible drop-out can explain the continuous reduction of METs, even in the observed post-home confinement period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the health-related quality of life (HRQoL) of patients with ulcerative colitis is considerably lower than that of the general population [24]. In addition, factors related to the quality of life of these patients are age at onset [5], age [6], sex [4, 68], disease activity [2, 3, 7, 914], disease type [3, 13], disease duration [15], anxiety [4, 12, 15], depression [2, 4, 12, 14, 15], psychological stress [8, 12], occupation [5, 9, 16], workplace support [17], and social life [18, 19]. Fu et al [20] examined the association between disease activity, social support, and HRQoL in patients with inflammatory bowel disease (IBD).…”
Section: Introductionmentioning
confidence: 99%